A lithium nickel manganese oxide cathode material, a lithium ion battery and a preparation method

By using a spherical secondary particle structure with alternating large and small particles and a nanopore design, the high-temperature cycle stability and compaction density of lithium nickel manganese oxide cathode materials were solved, achieving high energy density and long lifespan lithium-ion battery performance.

CN117594786BActive Publication Date: 2026-11-06XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311486583.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2026-11-06
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

Existing lithium nickel manganese oxide cathode materials exhibit poor cycle stability at high temperatures, low compaction density, and easily broken electrode particles, thus affecting the performance of lithium-ion batteries.

Method used

A spherical secondary particle structure is formed by alternating large and small primary particles, with nanopores distributed on the crystal surface. Grain growth is regulated through pre-sintering and sintering processes to form a lithium nickel manganese oxide cathode material with high solid density and excellent electrochemical performance.

Benefits of technology

It improves the compaction density and cycle stability of lithium nickel manganese oxide cathode material, buffers structural stress during charge and discharge, increases the active surface area and Li+ diffusion capacity, and enhances the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117594786B_ABST
    Figure CN117594786B_ABST
Patent Text Reader

Abstract

The application provides a lithium nickel manganese oxide positive electrode material, a lithium ion battery and a preparation method. The positive electrode material is a spherical particle structure, and includes secondary particles formed by staggered stacking of large particle primary particles and small particle primary particles. The large particle primary particles and / or the small particle primary particles have nano-pore channel structures on crystal faces. The close spherical particle structure formed by staggered stacking of the two kinds of primary particles with different sizes increases the stability of the material structure. The existence of the small particle primary particles not only increases the specific surface area of the material, but also fills the gaps between the large particle primary particles, which helps to reduce the porosity and improve the compaction density. The nano-pore channel structures on the primary particles are beneficial to the contact and penetration of the electrolyte with the positive electrode material, so that the compaction density and the capacity of the lithium nickel manganese oxide positive electrode material are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and particularly to a lithium nickel manganese oxide cathode material, a lithium-ion battery, and a preparation method thereof. Background Technology

[0002] With the rapid development of modern technology, lithium-ion batteries have been widely used in many fields such as hybrid vehicles, electric vehicles, electric motorcycles, and smart grid systems. In order to further expand the application of lithium-ion batteries in the potential mass market of electric vehicles, there is an urgent need to develop new lithium-ion battery cathode materials with high energy density, high power density, long lifespan, and low cost to alleviate the increasing carbon dioxide emissions and noise pollution.

[0003] High-voltage lithium nickel manganese oxide (LNMO) cathode materials have become one of the most promising candidate cathode materials due to their advantages such as high energy density, low cost, and good environmental friendliness. However, the poor cycle stability at high temperatures hinders their commercial application. Currently, the main approach is to modify the morphology and structure of LNMO to improve its electrochemical performance. However, lithium nickel manganese oxide cathode materials prepared in existing technologies still suffer from low compaction density and particle breakage during electrode compaction, which in turn affects the cycle stability of the battery.

[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a lithium nickel manganese oxide cathode material, a lithium-ion battery, and a preparation method thereof.

[0006] According to a first aspect of the present invention, a lithium nickel manganese oxide cathode material is provided, wherein the lithium nickel manganese oxide cathode material has a spherical particle structure, comprising secondary particles formed by alternating stacking of large primary particles and small primary particles, wherein the crystal surfaces of the large primary particles and / or the small primary particles have nanopore structures.

[0007] In one exemplary embodiment of the invention, the average particle size ratio of the large primary particles to the small primary particles is 1:0.01 to 0.6.

[0008] In one exemplary embodiment of the invention, the volume of the primary particles is 20% to 70% of the total volume of the secondary particles; and / or, the specific surface area of ​​the secondary particles is 0.5 to 1 m². 2 / g.

[0009] In one exemplary embodiment of the invention, the nanopore structure is formed by a plurality of randomly distributed nanopores, the average pore size of the nanopores being less than or equal to 200 nm, and / or the nanopore structure is formed on the (100) crystal plane of the large primary particles and / or small primary particles.

[0010] In one exemplary embodiment of the invention, the compaction density of the lithium nickel manganese oxide cathode material is 3-3.5 g / cm³. 3 .

[0011] According to a second aspect of the present invention, a method for preparing the lithium nickel manganese oxide cathode material as described in any one of the above claims is provided, comprising:

[0012] S1, after mixing nickel manganese compound with molybdate, pre-sintering is performed to obtain intermediate product;

[0013] S2, the intermediate product is mixed with molybdate and lithium source and then sintered to obtain the sintered product;

[0014] S3. The sintered product is washed and dried to remove molybdate, thus obtaining lithium nickel manganese oxide cathode material.

[0015] In an exemplary embodiment of the invention, in step S1, the ratio of the total amount of Ni and Mn in the nickel-manganese compound to the amount of Mo in the molybdate is 1:(0.001 to 0.05); and / or, in step S2, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Mo in the molybdate is 1:(0.001 to 0.05); and / or, in step S2, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Li in the lithium source is 1:(0.5 to 0.7).

[0016] In an exemplary embodiment of the invention, in steps S1 and S2, the molybdate is selected from one or more of ammonium molybdate, sodium molybdate, and magnesium molybdate.

[0017] In an exemplary embodiment of the invention, in step S1, the pre-sintering parameters are: in an oxygen atmosphere, the temperature is increased to 300-550°C at a heating rate of 10-20°C / min and held for 1-6 hours; and / or, in step S2, the sintering parameters are: in an air atmosphere, the temperature is increased to 600-1000°C at a heating rate of 10-20°C / min and held for 6-12 hours.

[0018] According to a third aspect of the present invention, a lithium-ion battery is provided, comprising: a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the lithium nickel manganese oxide positive electrode material as described in any one of the above claims.

[0019] The beneficial effects of the lithium nickel manganese oxide cathode material, lithium-ion battery, and preparation method of the present invention are as follows:

[0020] The lithium nickel manganese oxide cathode material provided in this invention comprises spherical secondary particles composed of large primary particles and small primary ions tightly interleaved. This tight interleaving of large and small primary particles increases the compaction density, reduces porosity, and enhances the stability of the material structure, thus buffering the Li-ion reaction during charging and discharging. + The structural stress and volume changes caused by repeated insertion and extraction allow small primary particles to effectively fill the gaps, providing a large active surface area and a short particle diffusion distance, thus acting as a transport carrier for electrons and particles between particles.

[0021] Among them, the crystal surface of the primary particles also has a disordered distribution of nanopore structure, which is conducive to the contact and penetration of electrolyte and cathode material. Under the synergistic effect of the above special stacking structure and nanopore, the compaction density and cycle stability of lithium nickel manganese oxide cathode material are significantly improved.

[0022] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this disclosure and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a SEM image of the lithium nickel manganese oxide cathode material obtained in Example 1 of the present invention.

[0025] Figure 2 This is a SEM image of the lithium nickel manganese oxide cathode material obtained in Example 3 of the present invention.

[0026] Figure 3 The image shows the SEM image of the lithium nickel manganese oxide cathode material obtained in Comparative Example 1 of this invention.

[0027] Figure 4 The graph shows a comparison of the cycle performance of lithium nickel manganese oxide cathode materials obtained in Examples 1 and 3 and Comparative Example 1 of this invention. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions in the embodiments of this disclosure will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0029] The following provides a detailed description of the lithium nickel manganese oxide cathode material, lithium-ion battery, and preparation method according to embodiments of the present invention.

[0030] This invention provides a lithium nickel manganese oxide cathode material, which has a spherical particle structure, comprising secondary particles formed by alternating stacking of large and small primary particles. The large and / or small primary particles have nanopore structures on their crystal surfaces.

[0031] Specifically, the particle size of the large primary particles is larger than that of the small primary particles. Further, in one embodiment, D1 represents the average particle size of the small primary particles, and D2 represents the average particle size of the large primary particles; then, the ratio of D2:D1 is 1:0.01 to 0.6. For example, D2:D1 can be 1:0.01, 1:0.1, 1:0.2, 1:0.3, 1:0.6, etc.

[0032] Preferably, the ratio of D2 to D1 is 1:0.2 to 0.6, and more preferably, the ratio of D2 to D1 is 1:0.42 to 0.6. At this ratio, the small primary particles fill the gaps better, resulting in a more stable packing structure, which is beneficial to improving the material's cycle performance.

[0033] In one embodiment, V1 represents the volume of the primary particles and V0 represents the total volume of the secondary particles, then V1 is 20% to 70% of V0. For example, V1 is 25%, 50%, 60%, 70% of V0, etc.

[0034] More preferably, V1 is 40%–70% of V0; even more preferably, V1 is 50%–60% of V0. By adjusting the proportion of primary particles in secondary particles, the structural stability of the material can be better increased, and the Li2O3 content can be buffered during charging and discharging. + The volumetric strain resulting from insertion / extraction. Simultaneously, it acts as a transport carrier for electrons and particles between particles, improving the efficiency of Li. + Diffusion capability, increasing battery capacity.

[0035] In one embodiment, the specific surface area (BET) of the secondary particles in the cathode material is 0.5–1 m². 2 / g. For example, the BET of the cathode material is 0.55m. 2 / g, 0.71m2 / g, 0.85m 2 / g, 0.9m 2 / g, etc. Preferably, the BET of the positive electrode material is 0.6-0.9m. 2 / g, further preferably 0.7-0.87m 2 / g. A higher specific surface area facilitates better contact between the electrolyte and the cathode material, improving the battery's electrochemical performance. However, an excessively large specific surface area can negatively impact battery life. Maintaining the specific surface area of ​​the lithium nickel manganese oxide cathode material within the aforementioned range results in higher rate performance and a longer material lifespan.

[0036] In one embodiment, the lithium nickel manganese oxide material has an octahedral cross-section, with nanopores formed on the (100) crystal plane. It is understood that the nanopores can be formed only on the (100) crystal plane of either the large or small primary particles, or they can be formed on both the large and small primary particles' (100) crystal planes. Forming nanopores on the (100) crystal plane further enhances the reactivity of ions and accelerates Li... + The rate of diffusion.

[0037] In one embodiment, the nanopore structure is formed by multiple randomly distributed nanopores, with an average pore size less than or equal to 200 nm. For example, the average pore size of the nanopore structure is 5 nm, 100 nm, 150 nm, etc. The average pore size of the nanopore structure should not be too large, otherwise it may easily affect the structural stability of the material. The porous structure above the nanopores is Li. + It provides an effective diffusion channel and a shorter diffusion distance, while mitigating Li + Structural stress and volume changes caused by repeated insertion and removal.

[0038] In one embodiment, the compaction density of the lithium nickel manganese oxide cathode material is 3-3.5 g / cm³. 3 Furthermore, the preferred compaction density of the lithium nickel manganese oxide cathode material is 3.15–3.45 g / cm³. 3 More preferably, it is 3.2–3.4 g / cm³. 3 At this compaction density, the breakage of compacted electrode particles can be effectively reduced.

[0039] This invention also provides a method for preparing the above-mentioned lithium nickel manganese oxide cathode material, comprising:

[0040] S1, after mixing nickel manganese compound with molybdate, pre-sintering is performed to obtain intermediate product;

[0041] S2, the intermediate product is mixed with molybdate and lithium source and then sintered to obtain the sintered product;

[0042] S3. The sintered product is washed and dried to remove molybdate, thus obtaining lithium nickel manganese oxide cathode material.

[0043] The preparation method of lithium nickel manganese oxide cathode material in this embodiment involves pre-sintering at a lower temperature followed by sintering at a higher temperature. Molybdate is added stepwise during both the pre-sintering (S1) and sintering (S2) processes. Using molybdate as a grain growth regulator, the grain growth process is adjusted during both pre-sintering and sintering to form a morphological structure with alternating large and small primary particles. Furthermore, by adding molybdate in batches during the two sintering stages, excess molybdate accumulates on the grain surface, etching and forming pores, thereby creating a nanoporous structure on the grain surface of the lithium nickel manganese oxide cathode material.

[0044] In one embodiment, in step S1, the nickel-manganese compound can be selected from nickel-manganese hydroxides, such as Ni 0.25 Mn 0.75 (OH)2.

[0045] Further, in step S1, the ratio of the total amount of Ni and Mn in the nickel manganese hydroxide to the amount of Mo in the molybdate is 1:(0.001-0.055); more preferably, the ratio of the total amount of Ni and Mn in the nickel manganese hydroxide to the amount of Mo in the molybdate is 1:(0.025-0.045), and even more preferably, it is 1:(0.03-0.04).

[0046] Further, in step S2, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Mo in the molybdate is 1:(0.001 to 0.055); more preferably, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Mo in the molybdate is 1:(0.025 to 0.045), and even more preferably, it is 1:(0.03 to 0.04).

[0047] In steps S1 and S2, molybdate is added in batches. By adjusting the amount of molybdate added, the growth of large and small primary particles can be controlled. Furthermore, excess molybdate enriches the grain surface and forms nanopores through etching. Insufficient molybdate will not form enough nanopores, while excessive molybdate can easily lead to a decrease in material stability. When the molybdate is within the above-mentioned preferred ratio range, large and small primary particles of suitable size can be obtained, and the crystal faces of the primary particles can form suitable nanopore structures. Ultimately, the prepared lithium nickel manganese oxide cathode material possesses advantages such as high specific surface area, high compaction density, and excellent electrochemical performance.

[0048] Further, in steps S1 and S2, the molybdate may be selected from one or more of ammonium molybdate, sodium molybdate, and magnesium molybdate. Preferably, the molybdate is selected from sodium molybdate and / or magnesium molybdate.

[0049] It is understandable that molybdates with the same composition can be used in steps S1 and S2, or molybdates with different compositions can be used.

[0050] Furthermore, in step S2, the lithium source can be a lithium-containing compound, which includes, but is not limited to, one or more of lithium hydroxide, lithium carbonate, and lithium oxide. Specifically, the lithium source is preferably lithium carbonate and / or lithium hydroxide.

[0051] Further, in step S2, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Li in the lithium source is 1:(0.5 to 0.7); more preferably, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Li in the lithium source is 1:(0.5 to 0.6); and even more preferably, it is 1:(0.5 to 0.55).

[0052] Further, in step S1, the pre-sintering parameters are as follows: in an oxygen atmosphere, the temperature is increased to 300–550°C at a heating rate of 10–20°C / min, held for 1–10 hours, and then naturally cooled to room temperature to obtain a black solid intermediate product. Specifically, the pre-sintering time is preferably 1–6 hours.

[0053] Further, in step S1, the pre-sintering temperature is 300–550°C, more preferably 350–500°C, and even more preferably 400–500°C. The pre-sintering time is 3–8 h, more preferably 5–6 h. Further, the pre-sintering heating rate is 10–20°C / min, more preferably 15–20°C / min, and even more preferably 16–18°C / min.

[0054] Further, in step S2, the sintering parameters are as follows: in an air atmosphere, the temperature is increased to 600–1000°C at a heating rate of 10–20°C / min and held for 6–12 hours. After sintering, the product is cooled in the furnace to obtain a solid black powdery sintered product.

[0055] Further, in step S2, the sintering temperature is 800–1000℃, more preferably 877–950℃, and even more preferably 850–900℃. Further, the sintering holding time is 6–12 h, more preferably 8–11 h, and even more preferably 9–10 h. Further, the sintering heating rate is 10–20℃ / min, more preferably 15–20℃ / min, and even more preferably 16–18℃ / min.

[0056] By adjusting the temperature, holding time, and heating rate of the pre-sintering stage in step S1 and the sintering stage in step S2, the morphology and nanopore structure of the obtained cathode material can be controlled to ensure that the material has good electrochemical performance.

[0057] Further, in step S3, after sintering, the furnace is cooled to obtain a solid black powder. The black powder is dispersed in deionized water, filtered and washed once or multiple times to remove molybdate, and then dried to obtain spherical lithium nickel manganese oxide cathode material.

[0058] This invention also provides a lithium-ion battery, comprising: a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the aforementioned lithium nickel manganese oxide positive electrode material. The lithium-ion battery may further include a separator between the positive and negative electrodes. It is understood that lithium-ion batteries can be manufactured using known methods in the prior art.

[0059] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0060] Example 1

[0061] This embodiment provides a lithium nickel manganese oxide cathode material, which is obtained by the following steps:

[0062] (1) Ni 0.25 Mn 0.75 (OH)2 and sodium molybdate were thoroughly mixed with a total molar ratio of Ni and Mn to Mo of 1:0.03. The mixture was heated to the pre-sintering temperature of 450°C at a rapid heating rate of 15°C / min in an oxygen environment, held at the temperature for 6 hours, and then allowed to cool naturally to obtain a black solid intermediate product.

[0063] (2) The intermediate product obtained in step (1), sodium molybdate, and lithium carbonate are thoroughly mixed in a molar ratio of Ni and Mn, Mo and Li of 1:0.04:0.55. The mixture is heated to 900°C in air at a rapid heating rate of 15°C / min, held for 10 hours, and then cooled to room temperature in the furnace to obtain a black solid powder.

[0064] (3) Disperse the black solid powder obtained in step (2) in deionized water, filter, wash and dry to obtain spherical lithium nickel manganese oxide cathode material.

[0065] See Figure 1 As shown, Figure 1 The image shows a SEM image of the spherical lithium nickel manganese oxide cathode material prepared in Example 1.

[0066] Depend on Figure 1It can be seen that the spherical lithium nickel manganese oxide cathode material prepared in Example 1 is composed of secondary micron spherical particles formed by the close interleaving of large primary particles and small primary particles. At the same time, the (100) crystal planes of the large primary particles and small primary particles have a nanoporous structure.

[0067] Example 2

[0068] This embodiment provides a lithium nickel manganese oxide cathode material, which is obtained by the following steps:

[0069] (1) Ni 0.25 Mn 0.75 (OH)2 and sodium molybdate were thoroughly mixed at a molar ratio of Ni and Mn to Mo of 1:0.03. The mixture was heated to the pre-sintering temperature of 400℃ at a rapid heating rate of 10℃ / min in an oxygen environment, held at the temperature for 6 hours, and then allowed to cool naturally to obtain a black solid intermediate product.

[0070] (2) The intermediate product obtained in step (1), sodium molybdate, and lithium carbonate are thoroughly mixed in a molar ratio of Ni and Mn, Mo and Li of 1:0.03:0.55. The mixture is heated to 890°C in air at a rapid heating rate of 10°C / min, held for 8 hours, and then cooled to room temperature in the furnace to obtain a black solid powder.

[0071] (3) Disperse the black solid powder obtained in step (2) in deionized water, filter, wash and dry to obtain spherical lithium nickel manganese oxide cathode material.

[0072] The morphology of the lithium nickel manganese oxide cathode material prepared in Example 2 is basically the same as that in Example 1.

[0073] Example 3

[0074] This embodiment provides a lithium nickel manganese oxide cathode material, which is obtained by the following steps:

[0075] (1) Ni 0.25 Mn 0.75 (OH)2 and sodium molybdate were thoroughly mixed at a molar ratio of Ni and Mn to Mo of 1:0.01. The mixture was heated to the pre-sintering temperature of 450°C at a rapid heating rate of 15°C / min in an oxygen environment, held at the temperature for 6 hours, and then allowed to cool naturally to obtain a black solid intermediate product.

[0076] (2) The intermediate product obtained in step (1), sodium molybdate, and lithium carbonate are thoroughly mixed in a molar ratio of Ni and Mn, Mo and Li of 1:0.02:0.50. The mixture is heated to 900°C in air at a rapid heating rate of 15°C / min and held for 10 hours. The mixture is then cooled to room temperature in the furnace to obtain a black solid powder.

[0077] (3) Disperse the black solid powder obtained in step (2) in deionized water, filter, wash and dry to obtain spherical lithium nickel manganese oxide cathode material.

[0078] See Figure 2 As shown, Figure 2 This is a SEM image of the spherical lithium nickel manganese oxide cathode material prepared in Example 3 of the present invention.

[0079] Depend on Figure 2 It can be seen that, Figure 2 The prepared spherical lithium nickel manganese oxide cathode material consists of secondary micron-sized spherical particles composed of large and small primary particles that are tightly stacked together. However, the surfaces of the large and small primary particles are generally smooth and flat, with only a small number of nanopores present.

[0080] Comparative Example 1

[0081] This comparative example provides a lithium nickel manganese oxide cathode material, obtained by the following steps:

[0082] (1) Ni 0.25 Mn 0.75 (OH)2, sodium molybdate, and lithium carbonate were thoroughly mixed in a molar ratio of Ni and Mn, Mo, and Li of 1:0.02:0.55. The mixture was heated to 900°C in air at a rapid heating rate of 15°C / min, held at that temperature for 10 hours, and then cooled to room temperature in the furnace to obtain a black solid powder.

[0083] (3) Disperse the black solid powder obtained in step (2) in deionized water, filter, wash and dry to obtain lithium nickel manganese oxide cathode material.

[0084] See Figure 3 As shown, Figure 3 The image shows a SEM image of the spherical lithium nickel manganese oxide cathode material prepared in Comparative Example 1.

[0085] Depend on Figure 3 It can be seen that, Figure 3 The prepared lithium nickel manganese oxide cathode material is composed of secondary micron-sized spherical particles stacked together by primary particles of uniform size. The surface of the primary particles is smooth and flat, while there are a large number of voids between the primary particles.

[0086] Experimental Example 1

[0087] The physical properties of the lithium nickel manganese oxide cathode materials prepared in Examples 1-3 and the comparative examples were tested, and the test results are shown in Table 1.

[0088] Table 1

[0089]

[0090] Note 1: V1 represents the volume of the primary particles, and V0 represents the total volume of the secondary particles;

[0091] Note 2: D1 represents the average particle size of the primary particles of small particles, and D2 represents the average particle size of the primary particles of large particles.

[0092] As can be seen from Table 1, the lithium nickel manganese oxide cathode material obtained in this embodiment has a good compaction density. In particular, when the following conditions are met: the ratio of the total amount of Ni and Mn in the nickel manganese hydroxide to the amount of Mo in the molybdate during the pre-sintering process is 1:(0.03~0.04), and the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Mo in the molybdate during the sintering process is 1:(0.03~0.04), the obtained lithium nickel manganese oxide cathode material exhibits a better compaction density.

[0093] Experimental Example 2

[0094] The lithium nickel manganese oxide cathode materials obtained in Examples 1, 3, and Comparative Example 1 were used to fabricate button batteries, and their performance was tested. Details are as follows:

[0095] Preparation of button batteries: A. Lithium nickel manganese oxide positive electrode material, carbon black, and polyvinylidene fluoride are dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 90:6:4 to obtain a slurry. The slurry is coated onto aluminum foil, dried in an oven at 120℃, and then cut to obtain the positive electrode sheet; B. Electrolyte: LiPF6 concentration is 1 mol / L, and ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are added at a mass ratio of 1:1:1; C. Negative electrode: lithium metal sheet; D. Assemble into button batteries, and start electrical performance testing after standing for one day.

[0096] High-temperature cycling performance test method: Under an ambient temperature of 50℃, with a charge / discharge range of 3.5-4.95V (where the upper limit voltage UCV is -4.95V and the lower limit voltage LCV is -3.5V), a 0.5C cycling performance test is performed. A. Charge the coin cell battery at 0.5C constant current and constant voltage to UCV, with a cutoff current of 0.02C; B. Let the coin cell battery rest for 5 minutes, then discharge it at 0.5C constant current to LCV, and let it rest for 5 minutes; C. Repeat steps A and B above, cycling for 50 cycles.

[0097] The test results are shown in Table 2:

[0098] Table 2

[0099] project Example 1 Example 3 Comparative Example 1 Discharge capacity, mAh / g 136.2 134.5 133.1 High-temperature cycle capacity retention 98.2% 82% 78.5%

[0100] like Figure 4 The figures shown are comparative graphs of the 50°C high-temperature cycling performance of the batteries prepared in Example 1, Example 3, and Comparative Example 1. From Table 2 and... Figure 4 It can be seen that the lithium nickel manganese oxide cathode material obtained in the embodiments of the present invention has good high-temperature cycling performance, the cycle capacity retention rate of Example 1 reaches 98.2%, and it also has a high discharge capacity.

[0101] The above description does not cover all embodiments. The detailed description of embodiments in this disclosure is not intended to limit the scope of the claimed disclosure, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments in this disclosure without inventive effort are within the scope of protection of this disclosure.

Claims

1. A lithium nickel manganese oxide cathode material, characterized in that, The lithium nickel manganese oxide cathode material has a spherical particle structure, including secondary particles formed by alternating stacking of large primary particles and small primary particles, wherein the large primary particles and / or the small primary particles have nanopore structures formed on the (100) crystal plane. 2.The lithium nickel manganese oxide cathode material of claim 1, characterized in that, The average particle size ratio of the large primary particles to the small primary particles is 1:0.01~0.

6. 3.The lithium nickel manganese oxide cathode material of claim 1, wherein, the volume of the small primary particles is 20% to 70% of the total volume of the secondary particles; and / or, the specific surface area of the secondary particles is 0.5 to 1 m 2 / g. 4.The nickel-manganese lithium acid material of claim 1, characterized in that, The nanopore structure is formed by a plurality of randomly distributed nanopores, the average pore size of the nanopores being less than or equal to 200 nm, and / or the nanopore structure is formed on the (100) crystal plane of the large primary particles and / or the small primary particles. 5.The nickel-manganese lithium acid material of claim 1, characterized in that, The compaction density of the nickel-manganese lithium acid positive electrode material is 3-3.5 g / cm 3 .

6. A method for preparing the lithium nickel manganese oxide cathode material according to any one of claims 1 to 5, characterized in that, include: S1, after mixing nickel manganese compound with molybdate, pre-sintering is performed to obtain intermediate product; S2, the intermediate product is mixed with molybdate and lithium source and then sintered to obtain the sintered product; S3, the sintered product is washed and dried to remove molybdate, yielding lithium nickel manganese oxide cathode material. In step S1, the ratio of the total amount of Ni and Mn in the nickel manganese compound to the amount of Mo in the molybdate is 1:(0.001~0.05); and / or, in step S2, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Mo in the molybdate is 1:(0.001~0.05); and / or, in step S2, the ratio of the total amount of Ni and Mn in the intermediate product to the amount of Li in the lithium source is 1:(0.5~0.7).

7. The method for preparing lithium nickel manganese oxide cathode material according to claim 6, characterized in that, In steps S1 and S2, the molybdate is selected from one or more of ammonium molybdate, sodium molybdate, and magnesium molybdate.

8. The method for preparing lithium nickel manganese oxide cathode material according to claim 6, characterized in that, In step S1, the pre-sintering parameters are: in an oxygen atmosphere, the temperature is increased to 300-550°C at a heating rate of 10-20°C / min and held for 1-6 h; and / or, in step S2, the sintering parameters are: in an air atmosphere, the temperature is increased to 600-1000°C at a heating rate of 10-20°C / min and held for 6-12 h.

9. A lithium-ion battery, characterized by include: A positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the lithium nickel manganese oxide positive electrode material as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Lithium battery positive electrode material, preparation method thereof and lithium battery using positive electrode material

    CN107768639A

  • Lithium composite oxide sintered body plate

    CN113597689A